WACIKA FOR OPTIMIZING THE BALANCED UTILITY OF STRATEGIC MANAGEMENT ACCOUNTING - Susilawati, Made; Ludigdo, Unti; Irianto, Gugus; Baridwan, Zaki (Accounting Department,, 2019)
This study aims to examine wacika, the words of wisdom based on dharma, i.e. truth and virtues, used as a conceptual framework for Strategic Management Accounting (SMA). This postmodern qualitative research uses wacika as its instrument of analysis, focusing on guidelines for SMA according to local content. The analysis was conducted by comparing wacika values with the field data filtered through reflections. The results indicate that there are six wacika concepts found in the wacika-based SMA conceptual framework, which has three levels. The first level, the tattwa, is objectives, which contains one concept. The second level, the susila, contains two concepts of assumptions and two concepts of principles. The third level, the upacara, is the characteristics of information, containing one concept. This wacika-based framework provides a basis for practitioners to provide, communicate, and literate useful information to the management and provide both material and non-material benefits and positive energy.Â Keywords: management decisions, comparative analysis, reflection, cooperative, conceptual framework